REALITISASI PENDIDIKAN KARAKTER SEBAGAI WUJUD BUDAYA BELAJAR SISWA SEKOLAH DASAR - I Dewa Putu Sandat; I Nyoman Sueca (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
The activities that the teacher does are hard work, smart work, and sincere work, and discipline must be used as guidelines in character education in schools. This is very important, especially to achieve optimal results, so that students as the young generation have the expected high characteristics which is the hope of the Indonesian government. This is done is to prevent public concern over the loss of identity / character in students. With a high character so that it will bring moral learners rooted in philosophy, experience and have cultural and religious values of the Indonesian nation. Thus character education must be continuous and never ending (never ending process), as an integrated part of preparing the nation's generation, which is adapted to the human figure having a future. Character education must grow up the philosophy and practice of the whole character of this nation.. The character of the nation contains cultural that must be manifested in the cultural awareness and cultural intelligence of every citizen of the country.